Guidelines for Perioperative Care for Liver Transplantation: Enhanced Recovery After Surgery (ERAS) Recommendations. Issue 3 (March 2022) - Brustia, Raffaele; Monsel, Antoine; Skurzak, Stefano; Schiffer, Eduardo; Carrier, François Martin; Patrono, Damiano; Kaba, Abdourahamane; Detry, Olivier; Malbouisson, Luiz; Andraus, Wellington; Vandenbroucke-Menu, Franck; Biancofiore, Gianni; et al.
Abstract : Background: Enhanced Recovery After Surgery (ERAS) is a multimodal, evidence-based, program of care developed to minimize the response to surgical stress, associated with reduced perioperative morbidity and hospital stay. This study presents the specific ERAS Society recommendations for liver transplantation (LT) based on the best available evidence and on expert consensus Methods: PubMed and ClinicalTrials.gov were searched in April 2019 for published and ongoing randomized clinical trials on LT in the last 15 y. Studies were selected by 5 independent reviewers and were eligible if focusing on each validated ERAS item in the area of adult LT. An e-Delphi method was used with an extended interdisciplinary panel of experts to validate the final recommendations. Results: Forty-three articles were included in the systematic review. A consensus was reached among experts after the second round. Patients should be screened for malnutrition and treated whenever possible. Prophylactic nasogastric intubation and prophylactic abdominal drainage may be omitted, and early extubation should be considered. Early oral intake, mobilization, and multimodal-balanced analgesia are recommended. Conclusions: The current ERAS recommendations were elaborated based on the best available evidence and endorsed by the e-Delphi method. Nevertheless, prospective studies need to confirm the clinical use of the suggested protocol.